2019
DOI: 10.1111/fcre.12397
|View full text |Cite
|
Sign up to set email alerts
|

Judging the Other: The Intersection of Race, Gender, and Class in Family Court

Abstract: This critical ethnographic study of family court child maltreatment proceedings describes and illuminates the ways in which racial, gender, and class disadvantages can manifest on the ground as judges, attorneys, social service workers, and parents—joined often by gender but split by race and class—adjudicate cases. The findings suggest that intersectionality worked in ways that exponentially marginalized poor mothers of color in the courtroom. They were marginalized both through the rules of the adversarial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Studies of TJ principles in action in the Family Court context are rare. The three studies that were identified include observations in traditional family courts during child abuse and neglect proceedings (Lens, 2016(Lens, , 2017(Lens, , 2019, a family drug treatment court (Fay-Ramirez, 2015), and in a traditional family court during custody and visitation proceedings (Dollar, 2020). These studies collectively suggest that Family Court environments can be home to both therapeutically just and unjust practices.…”
Section: The Therapeutic Jurisprudence Differencementioning
confidence: 99%
See 3 more Smart Citations
“…Studies of TJ principles in action in the Family Court context are rare. The three studies that were identified include observations in traditional family courts during child abuse and neglect proceedings (Lens, 2016(Lens, , 2017(Lens, , 2019, a family drug treatment court (Fay-Ramirez, 2015), and in a traditional family court during custody and visitation proceedings (Dollar, 2020). These studies collectively suggest that Family Court environments can be home to both therapeutically just and unjust practices.…”
Section: The Therapeutic Jurisprudence Differencementioning
confidence: 99%
“…These courtrooms were more adversarial and formal. Parents were spoken about, not to, as the traditional attorney-judge dyad relationship was prioritized, and parents were sometimes silenced when they tried to speak (Fay-Ramirez, 2015;Lens, 2016Lens, , 2017Lens, , 2019. The emphasis, by judges or others, was on parental compliance rather than treatment, with judges sometimes chastising and admonishing parents (Fay-Ramirez, 2015;Lens, 2016Lens, , 2017.…”
Section: The Therapeutic Jurisprudence Differencementioning
confidence: 99%
See 2 more Smart Citations
“…For example, among trans people who have separated from a partner or spouse, 29% of Black parents report that courts or judges have limited or terminated their relationships with their children on the basis of their transgender identity or gender nonconformity; the same is true for 20% of multiracial, 17% of American Indian, 12% of White, and 9% of Latinx NTDS respondents (Grant et al, 2011; of note is that the Asian sample size for this question was too low to report). Such decisions unjustly sever parent-child bonds, with lasting consequences for these children and families (see Lens, 2019;Roberts, 2009). The healthcare system is another site of struggle for many trans parents and prospective parents, with implications for parent and child wellness and for trans people's pathways to parenthood.…”
Section: Portrait Of Lgbtq Parents Of Color: Demographic Characteristmentioning
confidence: 99%